Laparoscopic Hysterosacropexy: Is it a Safe Option for Fertility Spearing? - Paola Algeri; Laura Colonna; Silvia Bergamelli; Laura Imbruglia; Nunzia Mastrocola; Silvia Von Wunster (Tehran University of Medical Sciences, 2023)
Objective: In case of uterine prolapse, hyseroxacropexy, a conservative surgical approach, which allows the sparing of body image and sexuality, could be the choice in fertile women. Few information are reported on subsequent pregnancy after surgery. Case report: A 33 years-old women with symptomatic prolapse underwent a laparoscopic hysterosacropexy. Subsequently she expressed her pregnancy desire and she got pregnant. A scheduled caesarean section was performed without complication. The subsequent follow-up was regular: the patient was asymptomatic and presented no sign of prolapse recurrence. Conclusion: In motivate and well counselled patient, informed about the risk of prolapse recurrence, pregnancy could be considered after hysterosacropexy.